1992
DOI: 10.1002/mrd.1080330403
|View full text |Cite
|
Sign up to set email alerts
|

Developmental expression of the S35‐S45/SGP‐2/TRPM‐2 gene in rat testis and epididymis

Abstract: Testosterone-repressed prostate message-2 (TRPM-2) was originally isolated and cloned from the regressing ventral prostate of the rat. In this tissue, and in other hormone-dependent tissues such as the mammary gland, this gene is induced in the absence of the appropriate trophic hormone. Sequence analysis of the cDNA and genomic clones of TRPM-2 have demonstrated that the coding sequence of this gene is identical to S35-S45 (also known as SGP-2 and clusterin), which is constitutively expressed by the Sertoli c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

1992
1992
2008
2008

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…Although there is evidence that germ cells may produce ABP and SGP-2 [34,35], it seems unlikely that MSC-1 cells contain a contaminating germ cell line, since the cDNA probe for transferrin used on mRNA from MSC-1 cells did not detect a band in the region of hemiferrin, which is present in germ cells [36]. In addition, these cells do not express protamine associated with round and elongated spermatids [16].…”
Section: Discussionmentioning
confidence: 99%
“…Although there is evidence that germ cells may produce ABP and SGP-2 [34,35], it seems unlikely that MSC-1 cells contain a contaminating germ cell line, since the cDNA probe for transferrin used on mRNA from MSC-1 cells did not detect a band in the region of hemiferrin, which is present in germ cells [36]. In addition, these cells do not express protamine associated with round and elongated spermatids [16].…”
Section: Discussionmentioning
confidence: 99%
“…In mammalian spermatogenesis, apoptosis is common, and genetic disruptions of the Bax-Bcl-2 and other regulatory pathways distort spermatogenesis in usually predictable ways. However, fertility is often not completely disrupted, and spermatogenesis occasionally continues in the face of presumptive catastrophic interference with apoptosis, indicating that the decision-making regulation still functions and that alternative pathways can be found Zakeri et al, 1992;Knudson et al, 1995;Miller et al, 1997;Print and Loveland, 2000;Kierszenbaum, 2001;Sinha Hikim et al, 2003).…”
Section: Spermatogenesismentioning
confidence: 99%
“…It has subsequently been shown that clusterin is expressed in a wide variety of tissues undergoing apoptosis [74]. Although the expression of the gene is not confined exclusively to dying cells in other CATHE PSI NS COLLAGENASES b c systems (particularly the testis and liver [75][76][77]), it clearly plays an integral part in the death of prostatic secretory epithelial cells. While the role of clusterin in cell death is still not established firmly, the Protein appears to be involved in controlling cholesterol efflux from the membranes of the dying cells and facilitating the transfer of cholesterol to ApoA-I/HDL, and in protecting the membrane from complement fixation [ 7 8 ] .…”
Section: Extracellular Proteasesmentioning
confidence: 99%